Nutritional treatment – is it an issue in head and neck cancer patients? - Kawecki, Andrzej; Jagielska, Beata; Symonides, Małgorzata; Starościak, Stanisław (Contemporary Oncology/Współczesna Onkologia, 2004)
Nutritional disorders are recognised among a significant proportion of patients admitted to hospital, while still more patients develop it during hospitalisation. Approximately 30% of non-malnourished, non-oncological patients admitted to hospital will develop nutritional disorders during their stay, while in approximately 70% of patients showing signs of malnutrition on admission further nutritional disorders will appear during hospital stay. Among oncological patients some 75% show signs of malnourishment. It is assumed that 15-40% of them are already malnourished at the time of initial diagnosis. The pathogenesis of cancer cachexia is not yet clear. Its mechanisms include metabolic and non-metabolic disorders. Metabolic disorders present in the form of a clinical syndrome usually referred to as anorexia, while non-metabolic disorders mainly arise from side effects of oncological treatment. Nutritional status is one of the basic issues affecting the prognosis of oncological patients. It is also considered to be an important predictive factor. Despite the recent advances in medical sciences cancer cachexia continues to be an important clinical issue, while nutritional treatment is an important element of oncological therapy. Every patient suffering from a malignancy should undergo careful examination of his or her nutritional status and, if necessary, receive correct and applicable nutritional treatment.